Antidiabetic activities of 96% ethanol extract of Abelmoschus esculentus on Balb-C mice strain - Aditama, Agnis Pondineka Ria (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
Diabetes mellitus (DM) is a progressive metabolic disease that continues to increase every year. Treatment therapy using oral hypoglycemic drugs to treat DM has side effects, and alternative approaches must be taken. Abelmoschus esculentus has been known to be used as an alternative to DM because it has antioxidant activity due to its high flavonoid content. The purpose of this study was to determine the antidiabetic activity of 96% ethanol extract of Okra leaves against male mice of balb-c strain. Male mice were acclimatized for seven days and divided into five test groups and then fasted for 18 hours. Then the mice were induced with 150 mg / 20 g BW alloxan and measured on the 3rd day. Ethanol extract 96% okra leaves were then given in a dose of 5.6 mg / 20g BW; 11.2 mg / 20g BW; 22.4 mg / 20g BW, CMC Na 0.5% as negative control and glibenclamide 0.026 mg / 20g BBs as positive control for 14 days. The results of therapy with 96% ethanol extract of okra leaves can reduce blood glucose levels in mice so that the okra leaves contain flavonoid compounds that have antioxidant activity and can reduce blood glucose levels.